ETIKA DAN BERBAGI NASI DALAM MENGGUNAKAN MEDIA SOSIAL - Danang Nugroho; Wendi Saerul Qobar; Muhammad Roif Hasan Rofi'i; Muhammad Arif Hasan Rifa'i; Raihan Fajar Nurzaman; Muhammad Chrisan Angga (JURNAL ILMIAH RESEARCH STUDENT, 2024)
This study aims to determine how Sharing Rice in Bandung City fosters an attitude of social concern, especially in the people of Bandung City. Descriptive qualitative methodology was used in this research. Data was collected through in-depth interview techniques conducted in an unstructured manner. Data analysis begins with data reduction, presentation, and drawing conclusions. Triangulation technique is a technique of comparing data obtained through various methods. The results show that Sharing Rice in Bandung City builds an attitude of social care by providing a direct example to the community through sharing activities and inviting other people to share via social media. Apart from that, community members have spread sharing activities to other cities and 27 provinces.